ANN Current Controller Based on PI-Fuzzy Adaptive System for Shunt Power Active Filter. (29th August 2012) - Lamchich, Moulay Tahar
Abstract : This paper deals with the use of triphase shunt active filter which is able to compensate current harmonics, reactive power, and current unbalance produced by nonlinear loads. To perform the identification of disturbing currents, a very simple control method is introduced. It's formed by a DC voltage regulator and a balance between the average power of load and the active power supplied by the grid. The output current of the voltage source inverter (VSI) must track the reference current. This is done by a neural controller based on a PI-Fuzzy adaptive system as reference corrector. Also to regulate the DC link capacitor voltage a fuzzy logic adaptive PI controller is used.